The Impact of Psychological Factors on Women Entrepreneurial Inclination: Mediating Role of Self-Leadership - Linfang, Zhang; Khalid, Rimsha; Raza, Mohsin; Chanrawang, Noppadol; Parveen, Rehana (Frontiers in Psychology, 2021)
The worth of women’s entrepreneurship is accepted globally, but there is less focus on it in developing countries, and societal expectations mean women often lack the confidence to start their own business. The core purpose of this research is to investigate the influence of personality traits on women's inclination towards entrepreneurship. The personality traits are measured through the dimensions of openness, neuroticism, extraversion, conscientiousness, and agreeableness. Further, the study introduced the mediator of self-leadership on personality traits and entrepreneurial intentions of women. The study is quantitative in nature and used a questionnaire survey to collect the data by the convenience sampling technique. The data was collected in the context of Pakistan, and Smart PLS was chosen for further analysis. The findings revealed the significance of the relationship between personality traits and entrepreneurial intention. Furthermore, the study also highlighted the significance of self-leadership as a mediator and proposed significant relationships. The study suggested that personality issues should be considered and used from a business perspective, and self-leadership is important for women. The study provides room for policymakers and institutes to inform educational policies to motivate women entrepreneurs for the future.